Microbiological quality of fish thaw marketed in the City of São Luís, Maranhão (Research, Society and Development, 2022)
This research aimed to analyze, through microbiological characterization, the quality of the fish thaw from three markets located in the city of São Luis-MA. The fish thaw samples were collected in three markets located in the city center of São Luis-MA and sent to the Laboratory of Microbiology of Food and Water, at the Federal University of Maranhão, Campus São Luis. The parameters analyzed were: thermotolerant coliforms, Escherichia coli, Pseudomonas aueruginosa using the Most Probable Number (NMP) technique, with differentiation tests of the thermotolerants and reducing Clostridium sulfite using the layered technique. It was found that the samples analyzed showed a variation from 1100 to 2400 NMP/100 mL in the count of thermotolerant coliforms, while Pseudomonas aueruginosa showed a variation from 29 to 2400 NMP/100 mL. Of the total samples, 43.3% were contaminated with Escherichia coli and 56.7% with reducing Clostridium sulfite. It is concluded that the thaws of the analyzed fish were considered out of the standards according to the Ordinance No. 5/2017 of the Ministry of Health because it represents a risk to the health of the population.